Greatest Integer Function Integral

Calculus Level 5

8 1 x x 5 d x \large 8\int_{1}^{ \infty} \frac {\lfloor x \rfloor} {x^{5}}\, dx

If the value of the above integral is equal to π a b \dfrac { \pi^{a} } {b} , find the value of a + b a+b .

Notation: \lfloor \cdot \rfloor denotes the floor function .

Inspiration .


The answer is 49.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Anthony Muleta
Nov 19, 2015

Let I = 1 x x 5 d x I=\int _{ 1 }^{ \infty }{ \frac { \left\lfloor x \right\rfloor }{ { x }^{ 5 } } dx } .

8 I = 8 1 2 1 x 5 d x + 8 2 3 2 x 5 d x + 8 3 4 3 x 5 d x + . . . \Longrightarrow 8I=8\int _{ 1 }^{ 2 }{ \frac { 1 }{ { x }^{ 5 } } dx } +8\int _{ 2 }^{ 3 }{ \frac { 2 }{ { x }^{ 5 } } dx } +8\int _{ 3 }^{ 4 }{ \frac { 3 }{ { x }^{ 5 } } dx } +...

= 8 n = 1 n n + 1 n x 5 d x =8\sum _{ n=1 }^{ \infty }{ \int _{ n }^{ n+1 }{ \frac { n }{ { x }^{ 5 } } dx } }

= 8 n = 1 [ n 4 x 4 ] x = n x = n + 1 =8\sum _{ n=1 }^{ \infty }{ { \left[ \frac { n }{ -4{ x }^{ 4 } } \right] }_{ x=n }^{ x=n+1 } } \\

= 2 n = 1 ( 1 n 3 n ( n + 1 ) 4 ) =2\sum _{ n=1 }^{ \infty }{ (\frac { 1 }{ { n }^{ 3 } } -\frac { n }{ { (n+1) }^{ 4 } } ) } .

Now note that n ( n + 1 ) 4 = ( n + 1 ) 1 ( n + 1 ) 4 = n + 1 ( n + 1 ) 4 1 ( n + 1 ) 4 = 1 ( n + 1 ) 3 1 ( n + 1 ) 4 \frac { n }{ { (n+1) }^{ 4 } } =\frac { (n+1)-1 }{ { (n+1) }^{ 4 } } \\ =\frac { n+1 }{ { (n+1) }^{ 4 } } -\frac { 1 }{ { (n+1) }^{ 4 } } \\ =\frac { 1 }{ { (n+1) }^{ 3 } } -\frac { 1 }{ { (n+1) }^{ 4 } } .

So the sum is now equal to 2 n = 1 ( 1 n 3 1 ( n + 1 ) 3 + 1 ( n + 1 ) 4 ) = 2 n = 1 1 n 3 2 n = 1 1 ( n + 1 ) 3 + 2 n = 1 1 ( n + 1 ) 4 = 2 ζ ( 3 ) 2 ( 1 2 3 + 1 3 3 + 1 4 3 + . . . ) + 2 ( 1 2 4 + 1 3 4 + 1 4 4 + . . . ) = 2 ζ ( 3 ) 2 ( ζ ( 3 ) 1 ) + 2 ( ζ ( 4 ) 1 ) = 2 ζ ( 3 ) 2 ζ ( 3 ) + 2 + 2 ζ ( 4 ) 2 = 2 ζ ( 4 ) = 2 π 4 90 = π 4 45 2\sum _{ n=1 }^{ \infty }{ (\frac { 1 }{ { n }^{ 3 } } -\frac { 1 }{ { (n+1) }^{ 3 } } +\frac { 1 }{ { (n+1) }^{ 4 } } ) } \\ =2\sum _{ n=1 }^{ \infty }{ \frac { 1 }{ { n }^{ 3 } } } -2\sum _{ n=1 }^{ \infty }{ \frac { 1 }{ { (n+1) }^{ 3 } } } +2\sum _{ n=1 }^{ \infty }{ \frac { 1 }{ { (n+1) }^{ 4 } } } \\ =2\zeta (3)-2(\frac { 1 }{ { 2 }^{ 3 } } +\frac { 1 }{ { 3 }^{ 3 } } +\frac { 1 }{ { 4 }^{ 3 } } +...)+2(\frac { 1 }{ { 2 }^{ 4 } } +\frac { 1 }{ { 3 }^{ 4 } } +\frac { 1 }{ { 4 }^{ 4 } } +...)\\ =2\zeta (3)-2(\zeta (3)-1)+2(\zeta (4)-1)\\ =2\zeta (3)-2\zeta (3)+2+2\zeta (4)-2\\ =2\zeta (4)\\ =2\cdot \frac { { \pi }^{ 4 } }{ 90 } =\frac { { \pi }^{ 4 } }{ 45 } .

a = 4 , b = 45 a=4, b=45 and a + b = 49 a+b=\boxed {49} .

Chew-Seong Cheong
Sep 17, 2018

Relevant wiki: Riemann Zeta Function

Similar solution with @Anthony Muleta 's

I = 1 x x 5 d x = 8 k = 1 k k + 1 k x 5 d x = 8 k = 1 k 4 x 4 k + 1 k = 2 k = 1 ( k k 4 k ( k + 1 ) 4 ) = 2 k = 1 ( 1 k 3 k + 1 1 ( k + 1 ) 4 ) = 2 k = 1 ( 1 k 3 1 ( k + 1 ) 3 + 1 ( k + 1 ) 4 ) = 2 ( 1 + k = 1 1 ( k + 1 ) 4 ) = 2 ( 1 + k = 2 1 k 4 ) = 2 ( 1 + k = 1 1 k 4 1 ) = 2 k = 1 1 k 4 Riemann zeta function ζ ( n ) = k = 1 1 k n = 2 ζ ( 4 ) = 2 × π 4 90 = π 4 45 \begin{aligned} I & = \int_1^\infty \frac {\lfloor x \rfloor}{x^5}\ dx \\ & = 8 \sum_{k=1}^\infty \int_k^{k+1} \frac k{x^5}\ dx \\ & = 8 \sum_{k=1}^\infty \frac k{4x^4}\ \bigg|_{k+1}^k \\ & = 2 \sum_{k=1}^\infty \left(\frac k{k^4} - \frac k{(k+1)^4} \right) \\ & = 2 \sum_{k=1}^\infty \left(\frac 1{k^3} - \frac {k+1-1}{(k+1)^4} \right) \\ & = 2 \sum_{k=1}^\infty \left(\frac 1{k^3} - \frac 1{(k+1)^3} + \frac 1{(k+1)^4} \right) \\ & = 2 \left(1 + \sum_{\color{#3D99F6}k=1}^\infty \frac 1{\color{#3D99F6}(k+1)^4} \right) \\ & = 2 \left(1 + \sum_{\color{#D61F06}k=2}^\infty \frac 1{\color{#D61F06}k^4} \right) \\ & = 2 \left(1 + \sum_{\color{#3D99F6}k=1}^\infty \frac 1{k^4} \color{#3D99F6} - 1 \right) \\ & = 2 \color{#3D99F6} \sum_{k=1}^\infty \frac 1{k^4} & \small \color{#3D99F6} \text{Riemann zeta function }\zeta(n) = \sum_{k=1}^\infty \frac 1{k^n} \\ & = 2 {\color{#3D99F6} \zeta (4)} = 2 \times {\color{#3D99F6} \frac {\pi^4}{90}} = \frac {\pi^4}{45} \end{aligned}

Therefore, a + b = 4 + 45 = 49 a+b = 4+45 = \boxed{49} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...